Associations of urinary enterolignans and risk of overall and cause-specific mortality with or without serum albumin adjustment: a prospective cohort study - Sun, Zisuo; Wang, Qing; Shen, Tianyi; Zhu, Jingming; Wang, Hongli; Yang, Wanshui; Zhang, Zhuang; Zhou, Qiang (Frontiers in Nutrition, 2025)
BackgroundThe association between enterolignans (the bioavailable metabolites of dietary lignans) including enterolactone (ENL) and enterodiol (END) and long-term risk of mortality remains limited and inconclusive. Involvement of human serum albumin (HSA) could be a possible reason behind the inconsistency. We prospectively examined the associations between urinary enterolignans and the risk of overall and cause-specific mortality among US adults and evaluated the impact of adjusting for HSA by comparing the results before and after its inclusion as a covariate.MethodsThe data was obtained from the US National Health and Nutrition Examination Survey. Urinary END and ENL concentrations were measured using high-performance liquid chromatography with tandem mass spectrometric detection. Deaths from baseline until December 31, 2015 were identified through linkage to the National Death Index. Cox regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) with and without HSA adjustment. Joint analysis and stratified analysis were used to evaluated the impact of HSA on the associations of enterolignans with mortality risk.ResultsWe documented 1,578 deaths among 10,664 participants after a median follow-up of 9.8 years. Higher concentrations of ENL were associated with lower all-cause mortality risk (comparing extreme tertiles, HR = 0.86, 95% CI: 0.74–1.00, Ptrend = 0.031). However, the inverse association between urinary ENL and all-cause mortality risk became non-significant when further adjusting for HSA. Compared to individuals with low levels of both ENL and HSA, those with high levels of both ENL and HSA had the lowest mortality risk (HR = 0.71, 95% CI: 0.60–0.84). Meanwhile, urinary ENL concentrations were associated with decreased all-cause mortality risk (HR = 0.74, 95% CI: 0.59–0.93, Ptrend = 0.020) only in the group with higher HSA levels.ConclusionAdjustment of HSA attenuated the inverse association between urinary ENL and all-cause death risk to non-significance. HSA can be considered as an important covariate in the future epidemiological studies on enterolignans.